Development of pitting corrosion of steel pipes of water supply systems - V. A. Chukhin; N. A. Makisha (Vestnik MGSU)
Introduction. A research was conducted to study pitting corrosion, which precedes the appearance of fistulas in steel and cast-iron pipelines of water supply systems. The process of fistula formation includes the following phases: the formation of tubercles, the concentration of electrolyte inside the tubercles, the origin and development of stable pitting on the surface of corroding metal under the tubercles with further formation of holes in the walls of pipes.Materials and methods. The study was aimed at studying the role played by the dense layer that is one of the four structural elements of the tubercles. The dual effect of the dense layer on corrosion revealed. On the one hand, the presence of a dense layer protects the metal from further corrosion, on the other hand, it helps to create conditions under which corrosion turns from uniform to pitting.Results. It was experimentally established that during the corrosion process inside the tubercles, the concentration of the solution containing both components of the corroding metal (cations) and water in the pipes (anions) gradually increases. To explain the corrosion process occurring in the tubercle, a comparison of a dense layer of tubercles with an anion exchange membrane with selective properties was carried out, as a result of which the concentration of aggressive chloride ions increases in the structure of the tubercles. At the same time, due to the hydrolysis of the formed iron chloride and a decrease in pH, the corrosion rate increases significantly. The paper also discusses the formation of crystalline forms of corrosion products that are formed after removing pipes from the water supply system.Conclusions. The determining role played by one of the four structural elements of corrosion tubercles — a dense layer — was revealed. The proposed method for studying the corrosive sludge can be used to evaluate the effect of various corrosion inhibitors.